Effect of certain cryoprotectants on freezing of buffalo semen in milk dilutors - KUMAR, S; SAHNI, K L; MOHAN, GREESH; BISHT, G S (The Indian Journal of Animal Sciences, 2013)
Post-freezing per cent motile and per cent live sperm varied significantly in the presence of different sugars in a milk diluent containing different levels of yolk and glycerol. Optimum concentration of yolk was 5% and of glycerol 6%. Addition of many sugars, except fructose with different combinations of yolk and glycerol did not improve post-thaw motility (PTM) and live sperm. PTM was highest in milk containing 5% yolk + 6% glycerol + 1.0% fructose. PTM decreased significantly after addition of glucose, raffinose, common table sugar and xylose. Combination of higher yolk and glycerol depressed PTM. Per cent live sperm after freezing increased slightly after addition of fructose, whereas addition of other sugars decreased per Cent live sperm.